Arbitrage with Production, Collateral Constraint and Heterogeneous Belief - Ally Quan Zhang (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We construct a dynamic model economy in which households from segmented markets have varying financial asset demand. Intermediaries make profit by exploiting the price difference in segmented financial markets. However, intermediaries have to separately post their physical investment as collateral to trade. We show that the heterogeneous belief will disturb the intermediaries' self-recovery process in both financial and real sectors through endogenously determined collateral constraints. The dynamic interaction between belief determined collateral constraint and liquidity supply turns out to be a powerful transmission mechanism by which the effects of shocks persist, amplify and spill over to other sectors.
Keywords: E44; G01; P43; 330